Combined imaging and serum biomarkers in CEUS-guided microwave ablation for hepatocellular carcinoma: A meta-analysis - Zou, Xiaoli; Zhao, Danyi; Shang, Yu; Song, Yu; Deng, Yimei; Lu, Lin (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to evaluate the efficacy of a treatment strategy that actively integrates imaging features and serum biomarkers into contrast-enhanced ultrasound (CEUS)-guided microwave ablation (MWA) for hepatocellular carcinoma (HCC).MethodsA comprehensive literature search was conducted, and randomized controlled trials (RCTs) meeting the inclusion criteria were selected. The methodological quality of the included studies was assessed using the Cochrane Risk of Bias Tool, and RevMan 5.3 software was employed for meta-analysis. The primary endpoints included complete tumor ablation rate, local recurrence rate (LRR), local progression rate (LPR), recurrence-free survival (RFS), and complication rate.ResultsA total of seven RCTs involving 1,039 HCC patients (407 in the treatment group, 632 in the control group) were included. Meta-analysis demonstrated the following: The complete ablation rate was significantly higher in the treatment group than in the control group (risk ratio [RR] = 1.06; 95% confidence interval [CI] = [1.01, 1.10]; p = 0.010). The local recurrence rate was significantly lower in the treatment group (risk difference [RD] = − 0.09; 95% CI = [− 0.17, −0.01]; p = 0.02). No significant differences were observed in RFS (RR = 1.11; 95% CI = [1.00, 1.24]; p = 0.06), LPR (RR = 1.55; 95% CI = [0.78, 3.07]; p = 0.21), or complication rates (RR = 1.13; 95% CI = [0.66, 1.91]; p = 0.66) between the two groups. Heterogeneity among studies was low (I2 ≤ 34%), and funnel plot analysis indicated minimal publication bias.ConclusionCEUS-guided MWA combined with imaging features and serum biomarkers is associated with significant improvements in complete tumor ablation rates and a reduction in local recurrence. This strategy provides evidence-based support for optimizing precision local control in HCC, but its impact on long-term survival requires validation through future studies with extended follow-up.